Patterns of treatment failure in patients undergoing adjuvant or definitive radiotherapy for vulvar cancer. Issue 6 (June 2019) - Vorbeck, Christina Steen; Jhingran, Anuja; Iyer, Revathy B; Loft, Annika; Klopp, Ann; Mirza, Mansoor Raza; Sobremonte, Angela; Vedam, Sastry; Vogelius, Ivan Richter
Abstract : Objectives: Knowledge of the detailed pattern of failure can be useful background knowledge in clinical decision making and potentially drive the development of new treatment strategies by increasing radiotherapy dose prescription to high-risk sub-regions of the target. Here, we analyze patterns of recurrence in patients with vulvar cancer treated with radiotherapy according to original planning target volumes and radiation dose delivered. Methods: We analyzed dose-planning and post-treatment recurrence scans from patients with vulvar cancer treated at two institutions from January 2009 through October 2014. We delineated the recurrences and merged the dose-planning and recurrence scans for each patient by using deformable co-registration. We estimated the center of each recurrence on the merged scans with the goal of relating them to the original dose plan. Results: We evaluated 157 patients who received radiotherapy for vulvar cancer. Median age was 68 years (range 29–91). Patients with International Federation of Gynecology and Obstetrics (FIGO) stage IA-IVB were included. Twenty-nine patients had recurrent disease; 156 patients had squamous cell carcinoma and one patient had adenosquamous carcinoma of the vulva. Among the 157 patients, 37 patients with recurrent disease had recurrence scans available for review, for a total of 80 recurrence sites; 53% of the recurrences were located in the region to which the highest dose (60–70 Gy) had been prescribed. Patients who received definitive radiotherapy developed failure primarily in the high-dose region (80.5%), whereas patients who received adjuvant radiotherapy had a more scattered failure pattern (p<0.0001). Among the latter group, 29.5% failed in the high-dose region. Conclusions: Patients who received definitive versus adjuvant radiotherapy had different failure patterns, indicating that separate approaches are needed to improve both adjuvant and definitive radiotherapy for vulvar cancer.